2019
DOI: 10.1038/s41390-019-0720-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum levels of perfluoroalkyl substances in early pregnancy and offspring birth weight

Abstract: BACKGROUND: Perfluoroalkyl substances (PFASs) are widespread, bioaccumulating, and persistent and show placental transfer. Emerging research indicates associations between prenatal exposure and low birth weight. The aim of this study was to assess the associations between first trimester exposure to PFASs and birth weight (BW) in the Swedish Environmental, Longitudinal, Mother and child, Asthma and allergy (SELMA) study and examine whether associations differ between girls and boys. METHODS: Eight PFASs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 42 publications
5
62
0
Order By: Relevance
“…Serum concentrations of PFNA, PFOA and PFOS in early pregnancy corresponded well with those of other pregnant Swedish populations at the time, i.e. the SELMA study where samplings were performed 2007-2010 and PFAS were analysed at the same laboratory [47]. Thus, the generalisability of our findings to the general population of pregnant women should be high but they might not be applicable to preeclamptic pregnancies where cystatin C retention in blood is more pronounced [27].…”
Section: Discussionsupporting
confidence: 59%
“…Serum concentrations of PFNA, PFOA and PFOS in early pregnancy corresponded well with those of other pregnant Swedish populations at the time, i.e. the SELMA study where samplings were performed 2007-2010 and PFAS were analysed at the same laboratory [47]. Thus, the generalisability of our findings to the general population of pregnant women should be high but they might not be applicable to preeclamptic pregnancies where cystatin C retention in blood is more pronounced [27].…”
Section: Discussionsupporting
confidence: 59%
“…Linear models were parameterised to include covariates, MNI and concentrations of an endocrine disrupting chemical (log transformed) previously shown to be associated with the outcome variable; that is, PFOS with birth weight and BPF with WISC IQ. 8 17 We addressed the issue of the balance between good nutrition and dietary sources of toxicant exposures, as is the case for PFOS, in three steps: (1) We created a score for fish consumption using FFQ data. (2) We constructed an indicator variable for low and high fish consumption at varying cuts.…”
Section: Methodsmentioning
confidence: 99%
“…A more complex scenario is that a good diet may be a source for chemical exposure, as is the case with perfluoroalkyl acids (PFAAs), (eg, fish consumption is a source of perfluoro-octanesulfonic acid (PFOS) uptake) where prenatal exposure for several single PFAAs has been shown to be associated with a lower birth weight. 8 9 An interesting line of inquiry is measuring the balance between a healthy prenatal diet which may also be a source of environmental toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…In the SELMA-study we have previously shown associations between early pregnancy PFAS exposures, including PFOS, PFOA and PFNA, and preeclampsia as well as lower birth weight 9,14 . Within the same cohort we now add the novel finding of a positive association between first trimester PFOA exposure and increased risk for sporadic miscarriage during the second half of the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…In human, a continuously increasing number of publications reports associations between higher serum levels of several PFASs during pregnancy, especially perfluorooctane sulfonate (PFOS) together with perfluorooctanoic acid (PFOA), and preeclampsia [8][9][10] as well as reduced fetal growth [11][12][13][14] . Causation for such associations has however been questioned 13 .…”
mentioning
confidence: 99%